BEHAVIORAL EFFECTS OF ARONIA MELANOCARPAFRUIT JUICE IN EXPERIMENTAL ANIMALS WITH DIET-INDUCED METABOLIC SYNDROME - M. Abtulov; M. Eftimov; S. Marinova; M. Salbashian; M. Zhelyazkova-Savova; S. Valcheva-Kuzmanova (Trakia Journal of Sciences)
PURPOSE: This study evaluated the effects of polyphenol-rich Aronia melanocarpafruit juice (AMFJ) on the behavior of rats with metabolic syndrome (MS)induced by high-fat high-fructose diet. METHODS: Fifty rats were allocated into 5 groups (10 rats per group): control, MS, MS + AMFJ2.5, MS + AMFJ5and MS + AMFJ10. During the induction of MS in the course of 10 weeks, the last three groups were treated with AMFJ at doses 2,5 ml/kg, 5 ml/kg and 10 ml kg, respectively. The open field test was usedto examine locomotion, the social interaction test was used to evaluate anxiety, the depression-like state was studied by the forced swimming test and spatial memory was evaluated by the place recognition test. RESULTS: No differences were found in the overall motor activity across the groups. Anxiety and memory impairment were established in MS rats. AMFJ counteracted the development of anxiety, and brought the memory function back to normal. CONCLUSIONS: The improvement of the MS-induced behavioral alterations might be attributed to the rich polyphenolic content of AMFJ, essential for its antioxidant, anti-inflammatory and metabolic actions, and probably underlie also the anxiolytic and memory-enhancing effects observed in the present study.